2019
DOI: 10.1177/1046496419870600
|View full text |Cite
|
Sign up to set email alerts
|

Diminishing Returns of Leadership Behaviors on Leadership Emergence

Abstract: A large body of evidence has concluded that there are positive linear relationships between leadership behaviors and leadership emergence. Drawing on insights from the leadership and teams research, we hypothesized that above certain levels of task-oriented and relationship-oriented behaviors, such behaviors will have diminishing returns for leadership emergence. Hypotheses were tested using a sample of 105 leaderless teams within an assessment center setting. Our results indicate that team members’ behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 27 publications
(46 reference statements)
0
6
0
Order By: Relevance
“…The linkage between initiating structure (and similar types of task‐oriented behavior) and informal leader emergence has received widespread support in previous empirical research (e.g., Gerpott et al, 2019; Mitchell et al, 2019; Walter et al, 2012). A key reason underlying this relationship is that work teams are often focused on instrumental task accomplishment, and teammates are therefore likely to ascribe leadership qualities to members that provide valued contributions toward this goal (Gerpott et al, 2019; Van Vugt, 2006).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 93%
See 4 more Smart Citations
“…The linkage between initiating structure (and similar types of task‐oriented behavior) and informal leader emergence has received widespread support in previous empirical research (e.g., Gerpott et al, 2019; Mitchell et al, 2019; Walter et al, 2012). A key reason underlying this relationship is that work teams are often focused on instrumental task accomplishment, and teammates are therefore likely to ascribe leadership qualities to members that provide valued contributions toward this goal (Gerpott et al, 2019; Van Vugt, 2006).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 93%
“…Consideration includes behaviors such as looking out for others' welfare, showing concern, appreciation, and support, as well as being friendly and approachable (Bass & Bass, 2008; DeRue et al, 2011). Although initially developed in the context of formal leadership, research has repeatedly shown that members without official leadership authority can also demonstrate both initiating structure and consideration (and related types of task‐oriented and relations‐oriented behavior; e.g., Ellis, 1988; Mitchell et al, 2019; Walter et al, 2012). It seems likely, however, that formal supervisors versus nonsupervisory members may differentially enact these behaviors.…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
See 3 more Smart Citations